KONSTITUTIONALITAS DAN EFEKTIFITAS KEELEMBAGAAN WAKIL MENTERI DALAM KABINET MERAH PUTIH - Bagus, Moh.; Ma'ruf, Ari Naufal (Gapenas Publisher, 2024)
The role of Vice Ministers in Indonesia's government, as outlined in Presidential Regulation No. 139 of 2024, aims to assist Ministers in operational and technical tasks, allowing them to focus on strategic policies. This structure offers the potential to accelerate national development programs, especially in complex ministries. However, challenges arise, including overlapping authority between the Minister and Vice Minister, leading to decision-making confusion. Additionally, political appointments over expertise may hinder effectiveness. Clear regulations and merit-based appointments, along with strong oversight, are crucial to ensure optimal functioning. When well-regulated, Vice Ministers can improve inter-ministerial coordination, support efficient governance, and contribute to a more transparent and accountable government.